2021
DOI: 10.3390/ijerph18147573
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Acute Hypoxia on Lactate Thresholds and High-Intensity Endurance Performance—A Pilot Study

Abstract: The present project compared acute hypoxia-induced changes in lactate thresholds (methods according to Mader, Dickhuth and Cheng) with changes in high-intensity endurance performance. Six healthy and well-trained volunteers conducted graded cycle ergometer tests in normoxia and in acute normobaric hypoxia (simulated altitude 3000 m) to determine power output at three lactate thresholds (PMader, PDickhuth, PCheng). Subsequently, participants performed two maximal 30-min cycling time trials in normoxia (test 1 f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 18 publications
0
5
2
Order By: Relevance
“…It is already well documented that exercise performance for endurance-type efforts deteriorates in hypoxia (Amann et al 2006;Doubt 1991;Fornasiero et al 2018;Goodall et al 2022), whereas it is still controversial if this occurs in response to a cold stimulus (Castellani and Tipton 2016;Castellani and Young 2016), primarily due to different tested ambient temperatures. In our study, we found a 18% reduction in maximal exercise capacity in H, higher than the 10 to 13% decrease previously found for altitudes between 2500 and 3500 m (Faulhaber et al 2021;Friedmann et al 2004Friedmann et al , 2005Lorenz et al 2006;Ofner et al 2014;Weckbach et al 2019). However, WL reduction (-21%) at LT in H is in line with previous defined reduction in PO at LT in hypoxia (≈11 to 19% Faulhaber et al 2021;Weckbach et al 2019)), especially if considering greater simulated altitude in this study if compared to the others (3500 vs 3000 and 2650 m asl).…”
Section: Maximal and Lt Workloadcontrasting
confidence: 85%
See 1 more Smart Citation
“…It is already well documented that exercise performance for endurance-type efforts deteriorates in hypoxia (Amann et al 2006;Doubt 1991;Fornasiero et al 2018;Goodall et al 2022), whereas it is still controversial if this occurs in response to a cold stimulus (Castellani and Tipton 2016;Castellani and Young 2016), primarily due to different tested ambient temperatures. In our study, we found a 18% reduction in maximal exercise capacity in H, higher than the 10 to 13% decrease previously found for altitudes between 2500 and 3500 m (Faulhaber et al 2021;Friedmann et al 2004Friedmann et al , 2005Lorenz et al 2006;Ofner et al 2014;Weckbach et al 2019). However, WL reduction (-21%) at LT in H is in line with previous defined reduction in PO at LT in hypoxia (≈11 to 19% Faulhaber et al 2021;Weckbach et al 2019)), especially if considering greater simulated altitude in this study if compared to the others (3500 vs 3000 and 2650 m asl).…”
Section: Maximal and Lt Workloadcontrasting
confidence: 85%
“…As O 2max , also aerobic performance is consequently affected by environmental condition. The state of art regarding maximal incremental test in hypoxia shows a 10 to 13% decrease in peak power output (PPO) or maximal aerobic velocity (VAM) at altitudes between 2500 and 3500 m if compared to sea level (Faulhaber et al 2021 ; Friedmann et al 2004 , 2005 ; Lorenz et al 2006 ; Ofner et al 2014 ; Weckbach et al 2019 ), and the same happens at the intensities associated with the lactate thresholds, with a reduction ranging from 12 to 19% considering different detecting methods (Faulhaber et al 2021 ; Weckbach et al 2019 ). Similarly, Quirion et al (1989 ) found a 22% reduction in maximal WorkLoad (WL) and Oksa et al ( 2004 ) a 9% decrease in running performance time when exposed to − 20 °C if compared to + 20 °C.…”
Section: Introductionmentioning
confidence: 99%
“…The other aspect refers to a greater hematological stimulation promoted by hypoxia, which can be seen by the decrease of 32.5% in reticulocytes, concomitantly with the substantial increase of 28% of the off-score for HG. Faulhaber et al, 19 using a "single-blind" model, compared the effects of exposure to hypoxia (continuous and cyclic) on "key markers" of hematologic adaptation, stress, and cardiac damage in elderly people. Both hypoxia protocols lasted approximately 70 minutes, and SpO 2 severity was 85%.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to tourism, many individuals engage in work, business, or sports activities at high altitudes, such as skiing, trekking, and climbing. All these people have to deal with the challenges of high altitude hypoxia which induces various mountain sicknesses and impairs the mental and physical capacity of the natives and immigrants, especially among those with acute hypoxia exposure ( Netzer et al, 2013 ; Faulhaber et al, 2021 ; Forrer et al, 2021 ). Pharmacological prophylaxis by acetazolamide and modern preacclimatization strategies may be effective preparation options for the lowlanders to high altitude ( Burtscher et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%